Tradisi Bodo Contong sebagai Modal Sosial Kerukunan Umat Beragama pada Masyarakat Desa Rahtawu Kudus - Khafidhotunnur, Ulia; Farihah, Irzum (Prodi Aqidah dan Filsafat Islam, Fakultas Ushuluddin, Universitas Islam Negeri Sunan Kudus, 2019)
This article aims to determine the role of the Bodo Contong tradition as a social capital of harmony among religious communities in the multireligious community of Rahtawu Village. How does the community implement, interpret, and how the Bodo Contong tradition acts as social capital in the village of Rahtawu. This study uses a qualitative approach with interview methods conducted in the Rahtawu Village community. The results show that: First, the Bodo Contong tradition is one form of the realization of a balanced social system in a society that has religious differences. Second, the Bodo Contong tradition is a form of gratitude to God Almighty, as well as a tribute to the community towards the ancestors. Third, in the implementation of the Bodo Contong tradition, the values of capital are social trust, social norms and social networks that enable the community to carry out the Bodo Contong tradition together without blaming religious differences. Through the values of existing social capital, the people of Rahtawu Village can work together, respect and respect one another and can maintain harmony between religious communities.